1986
DOI: 10.1111/j.1600-0714.1986.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐oral salivary gland neoplasms: a retrospective study of 98 cases

Abstract: Chau MNY, Radden BG. Intra-oral salivary gland neoplastns: a retrospective study of 98 cases. .1 Oral Pathol 1986: \5: 339-342.The findings of a retrospeetive study of 98 tninor salivary tieoplasms are reported. The patients' ages ratiged from 13-79 years and there was an equal sex distribution. Sixty-one of the lesions were benign. 53 being pleomorphic adenotnas and 8 nionomorphic adenotnas. Of the tnalignant tumors. 19 were muco-epiderrnoid tumors. 12 adenoid eystie eareinomas. 4 adenoeareinornas, 1 careinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
32
7
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 13 publications
11
32
7
1
Order By: Relevance
“…Our figure of 66% is higher than the series in the United States (Spiro et al 1973;Chaudhry et al 1984 ;Regezi et al 1985) but appears to be almost the same as in Australia (Chau and Radden 1986) (Table 6). …”
Section: Discussioncontrasting
confidence: 62%
“…Our figure of 66% is higher than the series in the United States (Spiro et al 1973;Chaudhry et al 1984 ;Regezi et al 1985) but appears to be almost the same as in Australia (Chau and Radden 1986) (Table 6). …”
Section: Discussioncontrasting
confidence: 62%
“…The findings are in agreement with those of several studies that have pointed a percentage of PA of benign minor salivary gland neoplasms very close to 75% found in the present study 1,2,[9][10][11][12][13][14][15][16] . In addition, of the 18 cases found in this study, 10 occurred in the palate, demonstrating its high incidence in this location, as supported by several authors 9,11,12,15 .…”
Section: Discussionsupporting
confidence: 94%
“…In addition to these, the literature presents other possible signs and symptoms such as radiographic changes, ulcers, difficulty with normal oral functions and misfitting dentures 5,10,14,15 . The fact that the lesion had developed during an average period of 9.6 months before being recognized, and reached an average size of 2.1 cm, can be explained by its the silent nature of its growth 2,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Periodic acid Schiff (PAS) with and without diastase, A review of publications in English (MEDLINE 1966-2014) was performed, with all cases reported with clinical, histologic, immunophenotypic and/or follow-up information on CanAd evaluated and included in the review, but excluding ''Quiz'' or ''Case of the Month'' type reports. Several studies were excluded if no specific or separable information was given about CanAd or if the illustrations were not characteristic [23,51,55,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Several of the cases seemed to have been included multiple times in different series reports [9,10,40,[79][80][81][82][83].…”
Section: Methodsmentioning
confidence: 99%